Efeitos do óleo de milho e do sucralfato em equinos portadores de úlceras gástricas - Jose Ramon Martinez Aranzales (2012)
The Equine Gastric Ulcer Syndrome (EGUS) presents a high and variable occurrence in horses of different age groups and classes according to the activity they are carrying. The objective was evaluate the effects of corn oil and sucralfate in horses suffering from gastric ulcers. For this was used 15 horses divided into three groups. In the induction phase of ulcers, was used a combination of stall confinement and phenylbutazone (PBZ) in doses of 4.4 mg/kg/po/sid/5days with a single dose of 13.2 mg/kg/po on sixth day (GIII), single dose of 13.2 mg/kg/po on day six (GII) and the control group or untreated (GI). After the gastroscopy evaluation and laboratory tests was introduced the second stage treatment with the base of corn oil in the volume of 70-90ml/100kg (Gs II and III respectively) and the sucralfate 30mg/kg/tid (GI). Gastroscopy were performed, harvesting of gastric contents and biopsy of the area glandular gastric mucosa for analysis of PGE2, volatile fatty acids (VFAs) (acetic, propionic, butyric and lactic acids), pH and oxidant and antioxidant parameters (superoxide dismutase (SOD), n-acetylglucosaminidase (NAG), catalase (CAT), total glutathione (GSH), nitric oxide (ON), myeloperoxidase (MPO) and malondialdehyde (MDA). Gastric lesions of mild to moderate were induced in glandular and non-glandular area gastric mucosa in the groups that received PBZ. Treatments (corn oil and sucralfate) restored the ulcerated area of the glandular mucosa, but corn oil wasnt able to recover the non-glandular epithelium. Change from rising and falling of oxidants and antioxidant parameters were observed, but most of the variables did not present statistical difference between groups.